SPATIAL DISTRIBUTION OF WHITE-SPOTTED RABBIT FISH Siganus canaliculatus Parak, 1797 ON DIFFERENT SEAGRASS BEDS HABITAT OF THE INNER AMBON BAY (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
White-spotted rabbit fish Siganus canaliculatus is a type of demersal fish that is associated with the seagrass beds, both as a nursery ground, feeding ground and for protection from predators. The purpose of this study was to analyze the spatial distribution of S. canaliculatus in different seagrass beds. The research was conducted from August 2018 until July 2019 in the inner Ambon Bay. Fish samples were collected using beach seines. The measurement of the environmental parameters, was done as well at the same time. Statistic analysis showed in table, histogram, dendrogram, and biplot graphic. The results showed that as many as 1.050 white-spotted rabbit fish individual consisting of 598 males and 452 females, were found during the study. The environmental parameters are generally still supporting the life of S. canaliculatus had different preferences habitat based on its life cycle.  The adults size tend to be distributed in monospecific seagrass beds. On the contrary this result was inversely to the adult size that associated to mixed seagrass beds, and juvenile size, which was widely distributed on various habitats type that proves seagrass beds function as a nursery ground.